(untitled) - Evanovich, Janet (New York, 2014)
"Trenton, New Jerseys favorite used car dealer, Jimmy Poletti, was caught selling a lot more than used cars out of his dealerships. Now hes out on bail and has missed his date in court--and bounty hunter Stephanie Plum is looking to bring him in. Leads are quickly turning into dead ends, and all too frequently into dead bodies. Even Joe Morelli, the citys hottest cop, is struggling to find a clue to the suspected killers whereabouts. To top things off, Ranger--resident security expert and Stephanies greatest temptation--has been the target of an assassination plot. Hes dodged the bullet this time, but if Ranger wants to survive the next attempt on his life, hell have to enlist Stephanies help. Death threats, highly trained assassins, highly untrained assassins and Stark Street being overrun with a pack of feral Chihuahuas are all in a days work for Stephanie Plum"--
Keywords: Fiction; Plum, Stephanie; (Fictitious character); Bounty hunters; Fiction; Assassins; Fiction; Trenton (N.J.); Fiction; Detective and mystery fiction; Detective and mystery fiction